The General Concept of Fundamental Rights in the Jurisprudence of the European Court of Human Rights - K. A. Ryvkin (Московский журнал международного права, 2010)
The analysis of the European Court of Human Rights’ decisions shows a well-established concept of the essence of the rights listed in the European Convention on Human Rights. The Court is inspired by the idea of a free democratic society, which is transferred into the principle of the effective enjoyment of all the conventional rights by everyone. It constantly recalls that it is for the contracting states to strike a fair balance between the individual interests and the public interest in promotion of democracy. Doing so, under certain circumstances they may take measures constituting interference with the interests safeguarded by the Convention. The research of the European Court’s jurisprudence allows us to characterize both the functions of the conventional provisions in the national legal systems and the state’s obligations and rights of private persons derived from these provisions.